Adrenalectomy Lowers Incident Atrial Fibrillation in Primary Aldosteronism Patients at Long Term. Issue 4 (April 2018) - Rossi, Gian Paolo; Maiolino, Giuseppe; Flego, Alberto; Belfiore, Anna; Bernini, Giampaolo; Fabris, Bruno; Ferri, Claudio; Giacchetti, Gilberta; Letizia, Claudio; Maccario, Mauro; Mallamaci, Francesca; Muiesan, Maria Lorenza; et al.
Abstract : Primary aldosteronism (PA) causes cardiovascular damage in excess to the blood pressure elevation, but there are no prospective studies proving a worse long-term prognosis in adrenalectomized and medically treated patients. We have, therefore, assessed the outcome of PA patients according to treatment mode in the PAPY study (Primary Aldosteronism Prevalence in Hypertension) patients, 88.8% of whom were optimally treated patients with primary (essential) hypertension (PH), and the rest had PA and were assigned to medical therapy (6.4%) or adrenalectomy (4.8%). Total mortality was the primary end point; secondary end points were cardiovascular death, major adverse cardiovascular events, including atrial fibrillation, and total cardiovascular events. Kaplan–Meier and Cox analysis were used to compare survival between PA and its subtypes and PH patients. After a median of 11.8 years, complete follow-up data were obtained in 89% of the 1125 patients in the original cohort. Only a trend ( P =0.07) toward a worse death-free survival in PA than in PH patients was observed. However, at both univariate (90.0% versus 97.8%; P =0.002) and multivariate analyses (hazard ratio, 1.82; 95% confidence interval, 1.08–3.08; P =0.025), medically treated PA patients showed a lower atrial fibrillation–free survival than PH patients. By showing that during a long-term follow-up adrenalectomized aldosterone-producing adenoma patients have a similar long-term outcome of optimally treated PH patients, whereas, at variance, medically treated PA patients remain at a higher risk of atrial fibrillation, this large prospective study emphasizes the importance of an early identification of PA patients who need adrenalectomy as a key measure to prevent incident atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.